KEANEKARAGAMA MORFOLOGIS TANAMAN SAGU (Metroxylon SP.) DI KABUPATEN LINGGA PROPINSI KEPULAUAN RIAU - Kholik Al Qodri ZD; Wawan ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
A research of morphological diversity of sago palm (Metroxylon sp) has been implemented in three District in the Riau Island Province, District of Lingga that District North Lingga and the District of East Lingga. The research was conducted from February to May 2015 with the aim of knowing the morphological diversity, distribution and sago population in Lingga regency of Riau Islands Province. The research used survey methods with an intentional sampling technique (purposive sampling) accordance with the criteria in 11 villages. Observations or data collected was primary data form and secondary data form. Primary data were obtained through interviews with sago farmers and measure directly to plant morphology in field. Secondary data were obtained from BAPPEDA (Badan Perencanaan dan Pembangunan Daerah), BPS (Badan Pusat Statistik) and the Department of Agriculture, Plantation, Forestry and Veterinary Office of Lingga Riau Islands Province. The research indacated that there are two types of sago discovered in the Lingga District of Riau Islands Province that Tuni / Runggamanu (Metroxylon Rumphii Martius) and Molat / Roe (Metroxylon Sagus Rottbol). Keywords: Identification, Morphological diversity, Sago